THE HISTORY OF INDIAN CULTURE AND STAGES OF DEVELOPMENT - Rustamkulovna , Safarova Tumaris (PT. Antis International Publisher, 2024)
Objective: This article aims to explore the historical development of Indian culture, focusing on key technological and intellectual advancements of the Harappan civilization, including their systems of measurement, script, and timekeeping methods. Method: A comprehensive review of archaeological findings, ancient texts, and historical records is employed to analyze the impact of these innovations on Indian culture and their broader implications. Results: The study reveals that the Harappans possessed a sophisticated system of measurement for length and weight, developed an original script, and made significant strides in astronomy, mathematics, and timekeeping with the use of sundials, water clocks, and a unique calendar. These developments highlight the advanced nature of early Indian civilization. Novelty: The article contributes to the understanding of the technological and intellectual contributions of ancient Indian cultures, emphasizing their role in shaping later scientific and cultural practices. It also offers insights into how these innovations influenced both contemporary and future cultures in the Indian subcontinent and beyond.